Systematic Literatur Review : Pengaruh Media Pop Up Book Dalam Pembelajaran PPKn Di Sekolah Dasar - Siti Noor Arofah; Ahmad Rifqi; Arif Budi Prasetya; Putri Imatriyani Sholekhah; Fina Fakhriyah; Erik Aditiya Ismaya (Lembaga Pengembangan Kinerja Dosen, 2023)
The success of any particular educational process is influenced by many different components, but the use of educational media is one of them. Learning through media is an interactive process that serves as a communication hub, making the learning that occurs as a result beneficial to students. One example is the use of Pop-Up Books in PPK instruction in Elementary Schools. The purpose of this study is to understand whether Pop up books exist or not to improve student learning outcomes. The method uses the (SLR) method for data analysis Data from a journal article that has been indexed by Google Scholar and additional research shows that there are 6 articles that discuss PPKN's PPKN Pop Up Book Media in Elementary Schools Learning Based on the analysis, we can conclude that using books Pop-up books have a positive impact on learning outcomes of Civics in public schools.